Community HIV clinicians' perceptions about HIV cure-related research in the Northwestern United States. Issue 1 (18th July 2022) - Sylla, Laurie; Patel, Hursch; Louella, Michael; Simoni, Jane; Dubé, Karine
Abstract: Background: Research on stakeholder perspectives of HIV cure research has involved people with HIV (PWH), who generally cite the importance of HIV clinician advice in making decisions about trial participation. However, there has been little exploration of non-researcher community HIV clinician perspectives, which are clearly critical to the success of HIV cure-related research. Objective: We aimed to learn how community HIV clinicians perceive HIV cure research and identify factors that would lead them to support or discourage HIV cure trial participation by their patients. Methods: We recruited a purposive sample of 12 community HIV clinicians in metro-Seattle, WA to participate in structured interviews. We completed 11 interviews via teleconference and received one written response. We used conventional content analysis to analyze the data. Results: Overall, community HIV clinicians were supportive of patient participation in HIV cure trials. Factors affecting support included knowledge of local trials, ease of referral, patient immune function and health stability, study risks and benefits, burden of study requirements, patient characteristics, patient life stability, potential impact on engagement in care, study communication plans, and beliefs that patients should have the autonomy to decide to participate. Participants had concerns about trials requiring treatment delays or interruptions and HIV transmission risk. While their knowledge of the field was limited, they were interested in learning more about open HIV cure trials. Conclusions: It would benefit the HIV cure research community if those leading HIV cure trials make stronger efforts to engage community clinicians who care for PWH, but are not active researchers, early in the trial design process. Such engagement prior to launching HIV cure trials will improve trial designs, leading to better enrollment and retention within these important studies.